Znaczenie uniwersytetów dla budowania zaufania społecznego - Nowakowska-Siuta , Renata (Studia Edukacyjne, 2024)
The article presents an intellectual examination of the contemporary university’s condition, with special emphasis on trust as a core aspect underpinning university culture. By highlighting key elements of the university’s culture during critical phases of its evolution, the author articulates the tensions between societal expectations of the university and its inherent tasks and values, as well as the cultivation of social trust within the institution in today’s world. Additionally, the article offers insights into the foremost issues related to the expectations placed on researchers and the scientific community by society and individuals. It advocates a re-evaluation of the university’s role, urging that it be perceived not merely as a corporate entity or administrative framework, but rather as a community grounded in shared values.